KOMODIFIKASI ANAK DALAM PROGRAM REALITY SHOW PENCARIAN BAKAT MENYANYI “IDOLA CILIK” (ANALISIS WACANA KRITIS NORMAN FAIRCLOUGH) - Hanifa Choirunisa (Universitas Mercu Buana, 2016)
Nowadays, talent search program has been shown on several television stations. Television utilizing the value of participant’s talent to be converted into exchange value. Commodification is the term of the practice of changing the use value to be the exchange value. One of the objects of commodification that used recently by television is children. Children seem to be an attraction for advertisers on television because they are easily shaped and influenced by the environment. This purpose of the research is to determine the forms of commodification in a Reality Show program of singing talent search Idola Cilik. To find these forms of commodification, this study uses the basic theory of media political economy owned by Vincent Mosco. This research method using critical discourse analysis belongs to Norman Firclough. This study used a qualitative approach with descriptive type. The results of this study discusses forms of commodification of children in the Reality Show program of singing talent search Idola Cilik based on theory of media political economy, such as children exploitation, children is required to perform a variety of activities to meet the content demand of a program . In addition, children are also used as a tool to raise the rate and share for TV station. The most visible form of commodification is the judging system with premium SMS poll. This study concludes that there are many forms of commodification in Reality Show program of singing talent search Idola Cilik. Television